2005
DOI: 10.1002/ijc.21488
|View full text |Cite
|
Sign up to set email alerts
|

Induction of human endometrial cancer cell senescence through modulation of HIF‐1α activity by EGLN1

Abstract: Previous observations indicate that transfer of human chromosome (chr.) 1 induces senescence of endometrial cancer cells. To identify the gene(s) responsible for the senescence, we first analyzed the structural integrity of the introduced chr. 1 in immortal revertant from chr.1-transferred HHUA cells. The data demonstrated a correlation between nonrandom deletions within the 1q31-qter region and reversion to immortality. Next, by using a panel of 12 microsatellite markers, we found high frequencies of loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 33 publications
(39 reference statements)
2
51
0
Order By: Relevance
“…Recent studies have shown that cells cultured under hypoxic conditions can acquire the ability to delay the onset of replicative senescence through a mechanism mediated, at least in part, by HIF-1 -dependent up-regulation of hypoxia response element -containing genes such as macrophage migration inhibitory factor (34,35). Although hypoxia may potentially act in a similar fashion to prevent the initiation or maintenance of drug-induced senescence, an alternative mechanism for hypoxia-induced resistance is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cells cultured under hypoxic conditions can acquire the ability to delay the onset of replicative senescence through a mechanism mediated, at least in part, by HIF-1 -dependent up-regulation of hypoxia response element -containing genes such as macrophage migration inhibitory factor (34,35). Although hypoxia may potentially act in a similar fashion to prevent the initiation or maintenance of drug-induced senescence, an alternative mechanism for hypoxia-induced resistance is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ectopic overexpression of PHD1 suppresses HIF-1a accumulation and tumor growth, 62 and immortality of human endometrial cancer cells is often associated with loss of PHD2, while re-introduction of PHD2 induced senescence. 63 Likewise, PHD3 is also a potential tumor suppressor. During normal development, many precursors of sympathetic neurons undergo apoptosis, for which PHD3 is uniquely essential.…”
Section: Biological Functions Of Phdsmentioning
confidence: 99%
“…The primary antibodies for SYTL4 and melanophilin were produced as described previously (63,64). Other primary antibodies were obtained from Santa Cruz Biotechnology (65,66). For immunoblotting, proteins were resolved by SDS-PAGE and transferred to nitrocellulose membranes (Whatman Schleicher and Schuell).…”
Section: Immunoblotting and Coimmunoprecipitationmentioning
confidence: 99%